The midwife's tale - Thomas, Samuel S. (St. Martin's Minotaur, 2013)
It is 1644, and Parliament's armies have risen against the king and laid siege to the city of York. Even as the city suffers at the rebel's hands, midwife Bridget Hodgson becomes embroiled in a different sort of rebellion.